INFLUENCE OF ACTIVE ENZYMES ON COTTON OIL REFINING PROCESS - R.X.Medatov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Effect of cellulases and proteinases on carbohydrates and proteins of black cotton oil is studied. Processing of crude cotton oil neutral proteinase in combination with cellulolytic enzymes positively influences enzymatic processes and increases degree of hydrolysis of proteins and carbohydrates. It is determined that processed by enzymes crude cotton oil easily is exposed to refining, and increased the yield of oil and improves physical and chemical quality of the final product.